Principles of ensuring energy security in the national security system of the state - Havryliuk, Ivan; Kliat, Yurii; Cherneha, Tetiana; Bashynskyi, Volodymyr; Zaiets, Oleksandr; Taran, Olha (Social Development and Security, 2024)
Purpose: defining the basic principles of ensuring energy security of the state and their key aspects. Method: the method of analysing the problems of the energy sector is used. Practical implications: the proposed basic principles of ensuring the energy security of the state and their key aspects can be used in the development of policy documents on the development of the energy sector of the state, determining ways to counteract negative external and internal factors, and conducting research on the energy security of the state. Papertype: theoretical.